PEMERTAHANAN NILAI BUDAYA MELALUI SASTRA - Habel Samakori (Balai Bahasa Provinsi Papua, 2019)
Papua has culture assests and ecology environment in pacific area. If we listen commonly, Papua area is the largest area in Indonesia with most varieties of local culture. But the existency of Papua etnicts not balance with locally holding culture system and confession of values and locally unsure by hereditary, as the warranty of existency of local culture. Formulate of literary holding in Papua was seen by deeph research, that is identify, inventarisation, study and pragmatic realize analizing without refuse their situation and condition. So, the writer use the taksonomi logics based on local culture anatomy by konsept structural and functional in substansi of locally value and unsure in Papua to create effective models, so it will create the holding and eternal local literary in Papua.